2017
DOI: 10.1002/mrc.4684
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the local distortions and EPR parameters for Cu2+ in xNa2O‐(30–x)K2O‐70B2O3 (5 ≤ x ≤ 25 mol%) glasses

Abstract: The local distortions and electron paramagnetic resonance parameters for Cu in the mixed alkali borate glasses xNa O-(30-x)K O-70B O (5 ≤ x ≤ 25 mol%) are theoretically studied with distinct modifier Na O compositions x. Owing to the Jahn-Teller effect, the octahedral [CuO ] clusters show significant tetragonal elongation ratios p ~19% along the C axis. With the increase of composition x, the cubic field parameter Dq and the orbital reduction factor k exhibit linearly and quasi-linearly decreasing tendencies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Our calculations suggest that A ‖ and A ⊥ is negative and positive, respectively (see Table ). There are many reports on the negative A ‖ and positive A ⊥ of the hyperfine structure constants for the tetragonally elongated [CuO 6 ] 10− octahedral clusters . Consequently, the signs of hyperfine structure constants were determined in this work and can be regarded as reasonable.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Our calculations suggest that A ‖ and A ⊥ is negative and positive, respectively (see Table ). There are many reports on the negative A ‖ and positive A ⊥ of the hyperfine structure constants for the tetragonally elongated [CuO 6 ] 10− octahedral clusters . Consequently, the signs of hyperfine structure constants were determined in this work and can be regarded as reasonable.…”
Section: Discussionsupporting
confidence: 58%
“…Consequently, the signs of hyperfine structure constants were determined in this work and can be regarded as reasonable. The studies of hyperfine structure constants for Cu 2+ ions in many crystals given κ is in the range 0.2 κ 0.5 . The adopted κ is in the range and can be regarded as suitable.…”
Section: Discussionmentioning
confidence: 99%
“…[9] and similar tetragonal [CuO 6 ] 10− clusters in Refs. [21][22][23][24][25][26][27] for Cu 2+ in many other crystals and can be regarded as rational. In addition, the investigations of hyperfine parameters for Cu 2+ in many crystals revealed that κ is in the range 0.2-0.35 [23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…This point is also supported by various Cu 2+ centers in ZnGa 2 O 4 [18], ZnSeF 6 • 6H 2 O [19] and Al 2 O 3 crystals [20], where the impurity Cu 2+ centers actually show tetragonal elongation distortion due to the JT effect. Even in oxide glasses materials, the doped Cu 2+ centers still exhibit TEO [10,21]. Thus, the local structure of the center may be described by the relative elongation ratio η along the C 4 axis due to the JT effect, and the Cu-O bond lengths parallel and perpendicular to the C 4 -axis are expressed as follows:…”
Section: Calculationmentioning
confidence: 99%
“…On the basis of the perturbation theory, the high-order perturbation formulas of EPR parameters (g factors g jj , g ⊥ and hyperfine structure constants A jj , A ⊥ ) for 3d 1 ions with the ground state 2 B 2g can determined from the two SOC parameters model and CF theory [23] :…”
Section: Calculationmentioning
confidence: 99%